Expression of Microtubule-Associated Proteins in Relation to Prognosis and Efficacy of Immunotherapy in Non-Small Cell Lung Cancer - Luo, Jieyan; Hu, Qipeng; Gou, Maling; Liu, Xiaoke; Qin, Yi; Zhu, Jiao; Cai, Chengzhi; Tian, Tian; Tu, Zegui; Du, Yijia; Deng, Hongxin (Frontiers in Oncology, 2021)
Background: Microtubule-associated proteins (MAPs) have been considered to play significant roles in the tumor evolution of Non-Small Cell Lung Cancer (NSCLC). Nevertheless, mRNA transcription levels and prognostic value of distinct MAPs in patients with NSCLC remain to be clarified. Methods: In this study, Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA) database, the Human Protein Atlas were utilized to analyze the relationship between mRNA/protein expression of different MAPs and clinical characteristics in NSCLC patients, including tumor type and pathological stage. The correlation between the transcription level of MAPs and overall survival (OS) of NSCLC patients was analyzed by Kaplan-Meier plotter. Besides, 50 frequently neighbor genes of the MAPs were screened out and constructed network via the cBioPortal and STRING dataset. Meanwhile, we performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis on the expression data of MAPs and their 50 frequently neighbor genes in NSCLC tissues. Furthermore, The Cancer Immunome Atlas (TCIA) was utilized to analyze the relationship between MAPs expression and the response to immunotherapy. Finally, we used qRT-PCR to verify the expression of MAPs in 20 patients with NSCLC. Results: The present study discovered that the mRNA transcription levels of MAP7/7D2 were enriched in NSCLC tissues, while that of the MAP2/4/6/7D3 were lower in NSCLC specimens than in control specimens. The mRNA transcription level of MAP6 was significantly associated with the advanced stage of NSCLC. Besides, survival analysis indicated higher mRNA expressions of MAP2/4/6/7/7D3 were correlated considerably with favorable OS of NSCLC patients, whereas increased mRNA expression levels of MAP1A/1S were associated with poor OS. Moreover, the expression of MAP1A/1B/1S/4/6/7D1/7D3 were significantly correlated with Immunophenoscore (IPS) in NSCLC patients. Conclusions: Our analysis indicated that MAP1A/1S could serve as potential personalized therapeutic targets for patients with NSCLC, and the enriched MAP2/4/6/7/7D3 expression could serve as biomarkers for favorable prognosis in NSCLC. Besides, the expression of MAP1A/1B/1S/4/6/7D1/7D3 were closely related to the response to immunotherapy. Taken together, MAPs expression has potential application value in the clinical treatment and prognosis assessment of NSCLC patients, and further verifiable experiments can be conducted to verify our results.